What Did the Old Poor Law Really Accomplish? A Redux - Avner Greif; Murat Iyigun (Institute for the Study of Labor (IZA), 2013)
This paper examines the evolving effects of England's Old Poor Law (1601-1834). It establishes that poor relief reduced social unrest from around the late-17th century through the turn of the 19th century, at which point it began to spur population growth and its social stability effects dissipated. These conclusions are based on a new dataset encompassing 39 English counties from 1650 to 1815. It includes observations on the amount of poor relief offered, occurrences of food riots and other types of social unrest, population growth and a host of other variables. The paper first documents that county-level variations in poor relief had a statistically significant and quantitatively meaningful non-monotonic impact on population growth. Aid to the poor reduced population growth through the 1780s or 1820s when it began to exert significantly positive effects. Moreover, the Old Poor Law reduced food riots in the late-17th century and through most of the 18th century, but this effect dissipated in the early 19th century when poor relief began to generate population growth. Our analyses, thus, establish that the Old Poor Law fostered social order and stability for more than a century after which the Malthusian income effects dominated.
Keywords: N0; N33; O10; 330; social institutions; Malthus; social stability; economic development